Reimagining Global Health: Accelerating Change for a Sustainable Future - Melissa Salm; Ala Alwan; Maureen Lichtveld; Patricia J. García; Peter H. Kilmarx; Nelson K. Sewankambo; Rebecca Martin; Tahmeed Ahmed; Judith N. Wasserheit (Annals of Global Health, 2025)
In 2023, an interdisciplinary group of global health experts from five continents convened a plenary panel at the Consortium of Universities for Global Health (CUGH) annual conference entitled “Reimagining Global Health for the 21st Century.” At the heart of this viewpoint article lies a fundamental question: How can we reimagine global health to best confront existing challenges and meet the demands of the future? To fully assess the scope of global health challenges and identify sustainable solutions, a clear definition of the aims and strategic approaches is needed. Such an assessment is also critical for progress in promoting equity, including decolonizing global health. Key issues examined are the following: equity, governance, research, education, and sustainability. To assure a sustainable global health enterprise, we propose the following three strategic imperatives as guiding principles: a holistic, unified approach grounded in mutual benefit, joint investment, long-term collaborative commitment, and solidarity across low- to middle-income countries (LMICs) and high-income countries (HICs); joint priority setting of investments in research, education, practice, and workforce development; and collaborative governance, maximizing a multisectoral approach among local, national, regional, and global strategies. The viewpoint sets the stage for the development of an action roadmap to develop a unified concept of global health; identify strategies to ensure sustained funding for global health research, education and training, and practice; establish benchmarks and metrics to measure progress; and design a collaborative governance system to promote interconnectedness and engagement among local, regional, national, and global stakeholders.